Internal shari’ah audit in Malaysia: perceived effectiveness, determinants and implication on non- shari’ah non-compliance risk - Zainal Abidin, Nor Hafizah; Mohd Ariffin, Noraini (2018)
Shari’ah audit and Shari’ah review functions provide assurance to stakeholders of lslamic banks but at different lines of defense in mitigating Shari’ah non-compliance events. The paper compares the practice of Shari’ah audit and Shari’ah review in a full-fledged Islamic bank in Malaysia using case study method where the informants are Shari’ah auditors and reviewers. The study concentrates on the scope of audit, techniques adopted by the internal auditors and the reporting channel for audit findings and report. Based on discussion with internal Shari’ah auditors and reviewers, Shari’ah audit practice resembles Shari’ah review in terms of compliance checking against Shari’ah Resolution and Shari’ah Compliance manual, rather than focusing on Shari’ah governance, risk management and internal control for Shari’ah compliance. The findings reflect Shari’ah audit practice at an early state of adoption, where the emphasis is more on compliance checking rather than scrutinizing on internal control measures as the measures are not well implemented and developed within the Islamic bank. Further, Shari’ah auditors’ necessary skills to perform Shari’ah audit in a holistic manner is still in progression as there is lack of Shari’ah audit certification programme available in the industry. The findings indicate the urgent need for the regulator to issue technical guidance on scope and performance of Shari’ah audit for a more effective and value added role of Shari’ah auditors. Additionally, a formalized training and certification programme is also needed to enhance the competency level of Shari’ah auditors.